Supportive Educative Nursing Intervention (SENI) as Intervention in Enhancing Self-Efficacy among Hemodialysis Patients - Bardah Wasalamah; Syahirul Alim; Dony Widyandana (Journal of Health Sciences and Medical Development, 2022)
Fluid restriction is the hardest regimen to follow in chronic kidney disease patients receiving hemodialysis, leading to an increase of Interdialytic Weight Gain (IDWG) with several complications. Supportive Educative Nursing Intervention (SENI) Orem's theory is innovative method with the goal of enhancing fluid restriction self-efficacy, and thus have a positive impact on controlling IDWG as an objective marker of fluid restriction adherence. This study aimed to determine the effect of Supportive Educative Nursing Intervention (SENI) on self-efficacy among CKD patients. This study adopted a quasi-experimental, pre and post test with control group design, which was conducted at the RSUD. Dr. M Yunus Bengkulu, Indonesia involving 80 hemodialysis patients. Self-efficacy was measured using the Indonesian Fluid Intake Appraisal Inventory (I-FIAI). Data were collected at baseline, 1 week, and 2 weeks after intervention. Data were analyzed using Repeated ANOVA. Repeated ANOVA test showed a statistically significant difference in mean score self- efficacy (p=0.000). An increase mean score self- efficacy of intervention group was higher than control group (p<0.05). Supportive Educative Nursing Intervention (SENI) Orem's theory increases self- efficacy of hemodialysis patients in fluid restriction.